Digital Marketing Strategy for Disaster Education Media During Floods - Elyana, Luluk; Winarni, Dyah Setyaningrum; Kurniawan, Ratna Dwi (Proceedings Series on Social Sciences & Humanities, 2025)
The fulfilment of logistical needs during floods is vital to address challenges such as access to clean water, medicines, drinking water, and hygienic ready-to-eat food. Desa Pasuruhan, located in Kayen Subdistrict, Pati Regency, faces unavoidable flooding every rainy season. Surrounded by the Kendeng mountains, the village's water source contains limestone, making it unfit for consumption. To mitigate these challenges, the Kosabangsa team from Universitas Ivet conducted a disaster education program from September to December 2024. The program targeted the village’s youth group (Karang Taruna Bina Sejahtera) to prepare the community for recurring floods. Materials included disaster mitigation guides and educational pocketbooks for various age groups, distributed through micro-teaching sessions, both in- person and online. An innovative disaster service website was also launched as part of the initiative, providing access to disaster education resources. This platform offers a scalable solution for broader applications, combining tailored theoretical knowledge with the specific needs of the region. Accessible to both local residents and the public, it represents a unique integration of education and technology, showcasing its potential to address disaster challenges through digital marketing strategies.